Estudo do comportamento estático e à fadiga de junta colada compósito polimérico e aço em diferentes tratamentos de superfície e sujeita à névoa salina aplicada como reparo na indústria do petróleo - Perrut, Valber Azevedo (2018)
This study evaluates the mechanical behavior of carbon fiber composite and steel adhesive joint used as repair of metallic structures with thickness loss due to corrosion in a marine environment. Furthermore, it investigates the effect of different surface preparations on the metallic substrate and degradation by salt spray and UV when subjected to static and dynamic loads. Experimental tests on bonded joints were performed in order to evaluate the static strength and fatigue life with and without degradation and with different surface treatments. Moreover, two types of steel plates were used: with and without corrosion, in order to assess the influence of the geometric profile of the steel surface on the mechanical behavior of the joint. The results showed that the performance of the machine treatment is similar to blasting and that the corroded joint geometry negatively affected the static strength and the fatigue lifetime. The main contribution of this work is the determination of the mechanical behavior of bonded joints in terms of mechanical strength and fatigue lifetime, when degraded in salt spray with two types of surface treatment, blasting and rotary impact machine. The second contribution was to address the possibility of repairing areas where it is not possible to apply blasting.